Application of fracturing technology to increase gas production in low-permeability hydrate reservoir: A numerical study - Shen, Peng-Fei; Li, Gang; Li, Xiao-Sen; Li, Bo; Zhang, Jin-Ming (Chinese Journal of Chemical Engineering, 2021)
Low temperature and low permeability are the challenges for the development of hydrate reservoirs in permafrost. The ice produced around the production well caused by high depressurization driving force reduces the gas production, and it is necessary to reduce the effect of ice production on gas production. In this work, a new combination of fracturing technology and depressurization method was proposed to evaluate the gas production potential at the site DK-2 in Qinghai-Tibet Plateau Permafrost. A relatively higher intrinsic permeability of the fracture zone surround the horizontal production well was created by the fracturing technology. The simulation results showed that the fracture zone reduced the blocking of production ice to production wells and promoted the propagation of production pressure. And the gas production increased by 2.1 times as the radius of the fracture zone increased from0 to 4 m in 30 years. Nearly half of the hydrate reservoirs were dissociated in 30 years, and greater than 51.7% of the gas production was produced during the first 10 years. Moreover, production behaviours were sensitive to the depressurization driving force but not to the thermal conductivity. The growth of gas production was not obvious with the intrinsic permeability of the fracture zone higher than 100 mD. The effect of ice production on gas production by fracturing technology and depressurization method was limited. (C) 2020 The Chemical Industry and Engineering Society of China, and Chemical Industry Press. Co., Ltd. All rigths reserved.